2004
DOI: 10.1124/mol.66.2.293
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2Inhibits the Phospholipase D Pathway Stimulated by Formyl-methionyl-leucyl-phenylalanine in Human Neutrophils. Involvement of EP2Receptors and Phosphatidylinositol 3-kinase γ

Abstract: Prostaglandin E 2 (PGE 2 ), originally discovered as a pro-inflammatory mediator, also inhibits several chemoattractant-elicited neutrophil functions, including adhesion, secretion of cytotoxic enzymes, production of superoxide anions, and chemotaxis. In this study, we have examined the effects of PGE 2 and prostaglandin E (EP) receptor-selective agonists/antagonists on several steps of the formyl-methionyl-leucyl-phenylalanine (fMLP)-induced phospholipase D (PLD) activation pathway in human neutrophils to elu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
24
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 45 publications
3
24
0
Order By: Relevance
“…Stimulation of PMNs or differentiated PLB-985 cells with fMLF also redistributed cytosolic Arf1 and Arf6 to membranes (4,9). Moreover, we showed that cytohesin-1 has a clear preference for Arf1 over Arf6 in vitro (10), and other biochemical assays also indicate that the preferred substrate of ARNO (55,56), cytohesin-1 (57), and Grp1 (58) is Arf1.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Stimulation of PMNs or differentiated PLB-985 cells with fMLF also redistributed cytosolic Arf1 and Arf6 to membranes (4,9). Moreover, we showed that cytohesin-1 has a clear preference for Arf1 over Arf6 in vitro (10), and other biochemical assays also indicate that the preferred substrate of ARNO (55,56), cytohesin-1 (57), and Grp1 (58) is Arf1.…”
Section: Discussionmentioning
confidence: 77%
“…Arf6 has also been shown to stimulate PLD through activation of fMLF receptors in differentiated PLB-985 cells (4), whereas the addition of myristoylated Arf1 or Arf6 and GTPgS in permeabilized HL60 cells stimulates PLD activity (67). Stimulation of PMNs or PMN-like cells with fMLF leads to activation of PLD and correlates with membrane recruitment of several phospholipase coactivators, including Arf1, Arf6, Rho GTPases, and protein kinase Ca (9). In this study, we took advantage of the inhibitor of cytohesins to evaluate the contribution of the cytohesin-1-Arf signaling pathway in fMLF-mediated activation of PLD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To analyze further the role of calcium and distinguish it from other fMLF receptor-induced transduction pathways, we evaluated the effect of ionomycin, a calcium ionophore that bypasses the receptor activation step, on the subcellular distribution of Munc13-4 in neutrophils. As described previously (38), fMLF induced a rapid and transient increase in [Ca 2ϩ ] c , whereas ionomycin induced a sustained and long-lasting increase in [Ca 2ϩ ] c (Fig. 3C).…”
Section: Calcium-dependent Recruitment Of Munc13-4 To Membranesmentioning
confidence: 71%
“…Apart from increasing cAMP biosynthesis, a downstream event following stimulation of EP2 receptors is activation of PI3K (45,46). Moreover, activation of PI3K can eventually lead to PKC activation (47,48).…”
Section: Discussionmentioning
confidence: 99%